DIFFICULTIES IN TRANSLATING MEDICAL TEXTS FROM ENGLISH INTO UZBEK AND RUSSIAN AND PARONYMS IN THEM - Saodatkhan Saidullayevna Khodjaeva (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article presents a review of scientific publications devoted to the study of the specific features of translating paronyms in medical texts. This paper examines the main linguistic and cognitive difficulties caused by paronyms in medical discourse, analyzes typical errors, and suggests strategies to improve translation accuracy. Examples are taken from pharmaceutical manuals, clinical documentation, and medical literature written in English.